Green Biocatalysis of Xylitol Monoferulate: Candida antarctica Lipase B-Mediated Synthesis and Characterization of Novel Bifunctional Prodrug - Federico Zappaterra; Francesco Presini; Domenico Meola; Chaimae Chaibi; Simona Aprile; Lindomar Alberto Lerin; Pier Paolo Giovannini (BioTech)
Natural compounds with significant bioactive properties can be found in abundance within biomasses. Especially prominent for their anti-inflammatory, neuroprotective, antibacterial, and antioxidant activities are cinnamic acid derivatives (CAs). Ferulic acid (FA), a widely studied phenylpropanoid, exhibits a broad range of therapeutic and nutraceutical applications, demonstrating antidiabetic, anticancer, antimicrobial, and hepato- and neuroprotective activities. This research investigates the green enzymatic synthesis of innovative and potentially bifunctional prodrug derivatives of FA, designed to enhance solubility and stability profiles. Selective esterification was employed to conjugate FA with xylitol, a biobased polyol recognized for its bioactive antioxidant properties and safety profile. Furthermore, by exploiting t-amyl alcohol as a green solvent, the enzymatic synthesis of the derivative was optimized for reaction parameters including temperature, reaction time, enzyme concentration, and molar ratio. The synthesized derivative, xylitol monoferulate (XMF), represents a novel contribution to the literature. The comprehensive characterization of this compound was achieved using advanced spectroscopic methods, including 1H-NMR, 13C-NMR, COSY, HSQC, and HMBC. This study represents a significant advancement in the enzymatic synthesis of high-value biobased derivatives, demonstrating increased biological activities and setting the stage for future applications in green chemistry and the sustainable production of bioactive compounds.